Validation and simulation of cavitation flow in a centrifugal pump by filter-based turbulence model. Issue 1 (31st December 2022) - Cao, Weidong; Jia, Zhixiang; Zhao, Zhenjiang; Zhou, Ling
Abstract : The simulation of cavitation flow is sensitive to the turbulence model and cavitation model. To improve the accuracy of numerical simulation, a centrifugal pump with specific speed of 56.5 is taken as the research object, and the Filter-Based Model (FBM) was used to correct the RNG turbulence model. Zwart-Gerber-Belamri (ZBG) cavitation model, Kunz model and Schnerr-Sauer model were employed for the simulation of cavitation flow in a centrifugal pump. According to the comparison, the results calculated by the ZGB model were 8% closer to the experimental results in cavitation predictions. The cavitation occurs around the impeller ring and balance holes firstly, and then the vapor develops and cover 80% of the blade suction side. By using Q -criterion, the distribution of the vortex core region under different cavitation conditions were investigated. The volume of high intensity vortex under severe cavitation condition is 30%∼50% higher than that under other conditions. Furthermore, the distribution of the radial force of the impeller corresponds to the number of blades, and the cavitation affects the resultant force direction of the impeller. With the intensification of cavitation, the radial force of impeller increases gradually, and the regularity of radial force direction will be disorder.